Durability of Hepatitis B surface antigen seroclearance in patients experienced nucleoside analogs or interferon monotherapy: A real-world data from Electronic Health Record - Shi, Zongqi; Zheng, Huizhi; Han, Miaomiao; Hu, Jieli; Hu, Yuan; Li, Xiaosong; Zhu, Wenyan; He, Xinjun; Deng, Haijun; Long, Quanxin; Huang, Ailong (Genes & diseases, 2023)
Little is known about the difference in durability of HBsAg seroclearance induced by nucleoside analogs (NAs) or by interferon (IFN). A real-world, retrospective cohort study was conducted. Patients were assigned into two groups: NAs monotherapy-induced HBsAg seroclearance subjects and IFN monotherapy induced-HBsAg seroclearance subjects. A total of 198 subjects, comprised by 168 NAs monotherapy-induced and 30 IFN monotherapy-induced, who achieved HBsAg seroclearance were included in this study. The one-year probabilities of confirmed HBsAg seroclearance were significantly different in patients with NAs monotherapy and IFN monotherapy (0.960 (with 95% CI 0.922–0.999) vs. 0.691 (with 95% CI 0.523–0.913), log-rank-P = 4.04e-4). 73.3% (11 of 15) HBsAg recurrence occurred within one year after HBsAg seroclearance. The one-year probabilities of confirmed HBsAg seroclearance were higher in IFN monotherapy patients with anti-HBs than in IFN monotherapy patients without anti-HBs (0.839 (with 95% CI 0.657–1.000) vs. 0.489 (with 95% CI 0.251–0.953), log-rank test, P = 0.024). Our study thus provided novel insights into the durability of HBsAg seroclearance induced by NAs or IFN monotherapy. In particular, the HBsAg seroreversion rate was relatively high in IFN monotherapy subjects. The presence of anti-HBs was significantly correlated with a longer durability of functional cure induced by IFN treatment. And one-year follow-up in HBsAg seroclearance achieved individuals is proper for averting HBsAg seroreversion and other liver disease.